Nursing Care of Elderly People at Home and Ethical Implications: an experience from Istanbul - Doğan, Hanzade (Nursing ethics, 2004)
Elderly people are a particularly vulnerable group in society and have special health problems. The world population of older people is increasing. People who are 65 years or older constitute 6% of the Turkish population, 90% of whom have chronic health problems. In Turkey, there is a high possibility that elderly people’s requirements are not met by today’s health care system in the way they would wish. They prefer not to be hospitalized when they have health problems. From a wider perspective, various countries are still seeking how to provide the best care for elderly people. Our goal was to characterize home-based care for elderly people using an ethical approach as an area of interest for nurses and other health care professionals now and in the future, both for Turkey specifically and from a global perspective. We studied four case histories and then prepared a composite scenario and a short questionnaire for elderly people living in a specific district of Istanbul to evaluate their expectations from the health care system. We compared our findings with situations in other countries and have proposed some practical solutions. The results showed that these older people preferred to receive nursing care at home instead of in hospital in Turkey, and also in many other countries. In this article we discuss our findings, comparing them with those in the literature, and suggest that there should be nursing care at home with insurance coverage while using a proper ethical approach.